1997
DOI: 10.1006/viro.1997.8511
|View full text |Cite
|
Sign up to set email alerts
|

ThetaxGene Sequences Form Two Divergent Monophyletic Lineages Corresponding to Types I and II of Simian and Human T-Cell Leukemia/Lymphotropic Viruses

Abstract: Evolutionary associations of human and simian T-cell leukemia/lymphotropic viruses I and II (HTLV-I/II and STLV-I/II) are inferred from phylogenetic analysis of tax gene sequences. Samples studied consisted of a geographically diverse assemblage of viral strains obtained from 10 human subjects and 20 individuals representing 12 species of nonhuman primates. Sequence analyses identified distinct substitutions, which distinguished between viral types I and II, irrespective of host species. Phylogenetic reconstru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
12
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 51 publications
3
12
0
Order By: Relevance
“…If a viral population shows higher genetic diversity, it is normally considered more ancient Fargette et al, 2006;Gessain et al, 1992;Giri et al, 1997;Koralnik et al, 1994;Moya & Garcia-Arenal, 1995). The historical record of disease may or may not be consistent with the extent of genetic diversity.…”
Section: Genementioning
confidence: 99%
“…If a viral population shows higher genetic diversity, it is normally considered more ancient Fargette et al, 2006;Gessain et al, 1992;Giri et al, 1997;Koralnik et al, 1994;Moya & Garcia-Arenal, 1995). The historical record of disease may or may not be consistent with the extent of genetic diversity.…”
Section: Genementioning
confidence: 99%
“…Simian T-lymphotropic virus type 1 (STLV-1) is closely related to HTLV-1 and infects several nonhuman primate species. Phylogenetic analysis of the conserved tax gene sequences indicates that STLV-1 and HTLV-1 are evolutionarily related (32). Furthermore, STLV-1 Tax and STLV-1 bZIP factor (SBZ) have functions similar to those of their equivalents from HTLV-1 (19,33).…”
mentioning
confidence: 99%
“…3). Clearly STLV OU-KA falls within the HTLV-I\STLV-I evolutionary cluster as described by Giri et al (1997) but constitutes an isolated member of the subcluster consisting of Asian STLV-I strains from India, Japan and Indonesia.…”
mentioning
confidence: 85%
“…Phylogenetic analyses of STLV and HTLV isolates have suggested that HTLV-II is genetically distinct and separated from a common ancestor virus before HTLV-I evolved from STLV during multiple interspecies transmissions (Koralnik et al, 1994 ;Saksena et al, 1994 ;Song et al, 1994). Also, there are indications for an Asian origin of the HTLV\STLV viruses (Song et al, 1994 ;Giri et al, 1997). For the great apes, chimpanzee, gorilla and orang-utan, STLVs have been characterized from the common chimpanzee (Pan troglodytes) (Koralnik et al, 1994) and the pygmy chimpanzee (P. paniscus) (Giri et al, 1994 ;Vandamme et al, 1996), while antibodies cross-reacting with STLV have been described in gorillas (Gorilla gorilla) (Ibrahim et al, 1995).…”
mentioning
confidence: 99%
See 1 more Smart Citation